Unraveling cell populations in tumors by single-cell mass cytometry. (February 2015) - Di Palma, Serena; Bodenmiller, Bernd
Graphical abstract: Highlights: Single-cell mass cytometry enables analyses of heterogeneous cell populations. Mass-tag cellular barcoding increases multiplexing capability and sample throughput. Imaging mass cytometry methods allow spatial-resolved measurements of tumor tissues. New computational tools help identifying cell subsets in heterogeneous populations. Mass cytometry can study links between cell phenotypes and tumor microenvironment. Abstract : The development of new biotechnologies for the analysis of individual cells in heterogeneous populations is an important direction of life science research. This review provides a critical overview of relevant and recent advances in the field of single-cell mass cytometry, focusing on the latest applications in the study of cell heterogeneity. New approaches for multiparameter single-cell imaging, alongside advanced computational tools for deep mining of high-dimensional mass cytometric data, are facilitating the visualization of specific cell types and their interactions in complex cellular assemblies, such as tumors, potentially revealing new insights into cancer biology.